2020
DOI: 10.1101/2020.06.18.160176
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phenome-scale causal network discovery with bidirectional mediated Mendelian randomization

Abstract: Inference of directed biological networks from observational genomics datasets is a crucial but notoriously difficult challenge. Modern population-scale biobanks, containing simultaneous measurements of traits, biomarkers, and genetic variation, offer an unprecedented opportunity to study biological networks. Mendelian randomization (MR) has received attention as a class of methods for inferring causal effects in observational data that uses genetic variants as instrumental variables, but MR methods rely on as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 55 publications
(75 reference statements)
1
13
0
Order By: Relevance
“…The LCV approach [34] is a special case of our model, where the causal effects are not included in the model, but they estimate the confounder effect mixed with the causal effects to estimate a quantity of genetic causality proportion (GCP). In agreement with others [10,35] , we would not interpret non-zero GCP as evidence for causal effect. Moreover, in other simulation settings LCV has showed very low power to detect causal effects (by rejecting GCP=0) (Fig S15 in Howey et al [36] ).…”
Section: Discussionsupporting
confidence: 91%
“…The LCV approach [34] is a special case of our model, where the causal effects are not included in the model, but they estimate the confounder effect mixed with the causal effects to estimate a quantity of genetic causality proportion (GCP). In agreement with others [10,35] , we would not interpret non-zero GCP as evidence for causal effect. Moreover, in other simulation settings LCV has showed very low power to detect causal effects (by rejecting GCP=0) (Fig S15 in Howey et al [36] ).…”
Section: Discussionsupporting
confidence: 91%
“…Our method can be easily implemented only using GWAS summary data, which is public available for the most phenotypes as the emergence of a large number GWAS studies with huge sample size. Published MR-based algorithm such as cGAUGE, requires the individual-level data and are thus not as easily available as the GWAS summary statistics, and is very time consuming [25]; BIMMER are implemented based on the complex inverse sparse regression and obtained an approximately estimation of DCE matrix, this require time roughly ࣩ(κ d 4 ) for d phenotypes [28]. In the result of simulation study 2-3, we found that the computing time of MRSL is only around 1/100 of BIMMER, and 1/1000 of cGAUGE, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Also, MRSL outputs the unbiased direct effect of each pair of variables. Moreover, MRSL can be applied into the structure with feedback loops between any two variables, because our main MR method IVW can powerfully deal with the case of bi-directional causal relationship between two variables [28,76]. Similar to MR analysis, GWAS summary data of d phenotypes should from the homogenous population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, we will aim to combine DeepMR with a causal network inference method such as our recent bimmer model [Brown and Knowles, 2020] to explicitly account for the influence of other assayed TFs on each pair. DeepMR would also benefit from accompanying tools for diagnosing when model-generated data deviates from or violates MR assumptions.…”
Section: Discussionmentioning
confidence: 99%